2019
DOI: 10.1097/aud.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinical Outcomes in Cochlear Implantation Using Glucocorticoid Therapy: A Review

Abstract: Cochlear implant surgery is a successful procedure for auditory rehabilitation of patients with severe to profound hearing loss. However, cochlear implantation may lead to damage to the inner ear, which decreases residual hearing and alters vestibular function. It is now of increasing interest to preserve residual hearing during this surgery because this is related to better speech, music perception, and hearing in complex listening environments. Thus, different efforts have been tried to reduce cochlear impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…In a previous study, we found a slight tendency for DPS to be more effective in reducing TNFα-production than other DEX formulations [16]. Moreover, other glucocorticoids such as prednisone and hydrocortisone (cortisol) offer therapeutic potential for inner ear therapy [51] and are promising for inclusion in further investigations.…”
Section: Biocompatibility and Bio-efficacymentioning
confidence: 99%
“…In a previous study, we found a slight tendency for DPS to be more effective in reducing TNFα-production than other DEX formulations [16]. Moreover, other glucocorticoids such as prednisone and hydrocortisone (cortisol) offer therapeutic potential for inner ear therapy [51] and are promising for inclusion in further investigations.…”
Section: Biocompatibility and Bio-efficacymentioning
confidence: 99%
“…According to the current clinical indications for cochlear implantation (CI), which have been progressively expanded, candidates for the procedure are those with partial deafness (PDT, partial deafness treatment), children with congenital profound hearing loss, single-sided deafness patients, and those over 65 years of age, as well as those with acquired bilateral sensory hearing loss [ 1 , 2 , 3 ]. Some years ago, it would be very challenging, or even impossible, to preserve residual hearing after CI surgery [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…DEX is used to treat many conditions, including rheumatoid arthritis, bronchial asthma, systemic lupus erythematosus, autoimmune diseases, shocks of various etiologies, skin allergic diseases (neurodermatitis, eczema), and chronic rhinosinusitis, as well as to suppress transplant graft rejection [5,18,34,[56][57][58][59][60][61][62][63][64]. DEX readily penetrates the conjunctiva, so it is one of the most commonly used GCs for the treatment of ocular conditions, including inflammation diseases of both the anterior (keratitis, blepharitis, allergic DEX has good oral bioavailability; it is rapidly and completely absorbed in the gastrointestinal tract and had an elimination half-life of 1-2 h. After intramuscular injection, DEX sodium phosphate is absorbed slowly, with the maximum plasma concentration reached after 7-9 h and an elimination half-life of 3-5 h. In the blood, 60-70% of the DEX binds to a specific transporter protein (transcortin).…”
Section: Introductionmentioning
confidence: 99%
“…DEX is used to treat many conditions, including rheumatoid arthritis, bronchial asthma, systemic lupus erythematosus, autoimmune diseases, shocks of various etiologies, skin allergic diseases (neurodermatitis, eczema), and chronic rhinosinusitis, as well as to suppress transplant graft rejection [5,18,34,[56][57][58][59][60][61][62][63][64]. DEX readily penetrates the conjunctiva, so it is one of the most commonly used GCs for the treatment of ocular conditions, including inflammation diseases of both the anterior (keratitis, blepharitis, allergic conjunctivitis, and dry eye) and the posterior (choroiditis, uveitis, age-related macular degeneration, diabetic macular edema, and diabetic retinopathy) segments [5,7,[65][66][67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%